DT-13 Ameliorates TNF-α-Induced Vascular Endothelial Hyperpermeability via Non-Muscle Myosin IIA and the Src/PI3K/Akt Signaling Pathway - Zhang, Yuanyuan; Han, Yuwei; Zhao, Yazheng; Lv, Yanni; Hu, Yang; Tan, Yisha; Bi, Xueyuan; Yu, Boyang; Kou, Junping (Frontiers in Immunology, 2017)
DT-13(25(R,S)-ruscogenin-1-O-[β-d-glucopyranosyl-(1→2)][β-d-xylopyranosyl-(1→3)]-β-d-fucopyranoside) has been identified as an important factor in TNF-α-induced vascular inflammation. However, the effect of DT-13 on TNF-α-induced endothelial permeability and the potential molecular mechanisms remain unclear. Hence, this study was undertaken to elucidate the protective effect of DT-13 on TNF-α-induced endothelial permeability and the underlying mechanisms in vivo and in vitro. The in vivo results showed that DT-13 could ameliorate endothelial permeability in mustard oil-induced plasma leakage in the skin and modulate ZO-1 organization. In addition, the in vitro results showed that pretreatment with DT-13 could increase the transendothelial electrical resistance value and decrease the sodium fluorescein permeability coefficient. Moreover, DT-13 altered the mRNA and protein levels of ZO-1 as determined by real-time PCR, Western blotting and immunofluorescence analyses. DT-13 treatment decreased the phosphorylations of Src, PI3K and Akt in TNF-α-treated human umbilical vein endothelial cells (HUVECs). Further analyses with PP2 (10 μM, inhibitor of Src) indicated that DT-13 modulated endothelial permeability in TNF-α-induced HUVECs in a Src-dependent manner. LY294002 (10 μM, PI3K inhibitor) also had the same effect on DT-13 but did not affect phosphorylation of Src. Following decreased expression of nonmuscle myosin IIA, the effect of DT-13 on the phosphorylations of Src, PI3K, and Akt was abolished. This study provides pharmacological evidence showing that DT-13 significantly ameliorated the TNF-α-induced vascular endothelial hyperpermeability through modulation of the Src/PI3K/Akt pathway and NMIIA, which play an important role in this process.